PENGARUH LAMA PERENDAMAN DAN MEDIA TABUR TERHADAP PERKECAMBAHAN BENIH MAHONI (Swietenia mahagoni (L) Jacq) - Zulkaidhah, Zulkaidhah; Umar, Husain; Kiptiah, Sarifatul (ForestSains, 2016)
The availability of water is a very important factor in the germination process. Therefore, it is necessary immersion process mahogany seeds to accelerate germination. The purpose of this study was to determine the effect of immersion time and media of sow to germination mahogany (Swietenia mahagoni (L) Jacq). This research was conducted from December 2015 to February 2016 at Permanent Nursery of BPDAS Palu – Poso, Tadulako University. This research applied a completely randomized design, factorial pattern with 9 treatments and 5 replications. The treatments of this research were immersion time that consist of 24 hours, 49 hours and 72 hours. Data were analyzed by analysis of variance and tested using Significant Difference test (LSD) with level 5%. The results of this study showed that immersion duration and media sow has significant effect on germination percentage, rate germination, root length and vigor, except the treatment of sow media has no significant effect on root length of mahogany seedling, and did not interaction between the two treatments. The highest germination percentages in treatment of immersion were 25 hours (P1) and 48 hours (P2) namely 56,87%, and 45,77%, respectively, and the lowest was 72 hours (P3) namely 24,43%. The fastest rates of germination for immersion treatment were 72 hours (P3) and 24 hours (P1) namely 17,73 days, 21,01 days respectively, and the latest was 48 hours (P2) namely 21,89 days. the longest roots were in the immersion treatments for 24 hours (P1), and 48 hours (P2) namely 9,26 cm, 8,63 cm respectively, and the shortest was in 72 hours (P3) namely 7,71 cm. The highest seed vigor was in the immersion treatment for 24 hours (P1) and 48 hours (P2) namely 50,23%, 39,11%, respectively, and the lowest was 72 hours (P3) namely 22,66%. The optimum of sow media for all parameters was sail + goat manure + carbonated rice husk.